Occurrence of Clinostomum Metacercariae in Oreochromis mossambicus from Mashoko Dam, Masvingo Province, Zimbabwe - Casper Mutengu; Wilson Mhlanga (Scientifica)
Mashoko Dam is in Ago-ecological Region 4 in Zimbabwe. Five sampling sites were randomly selected and each site was sampled twice per month, for six months. A total of 180 Oreochromis mossambicus fish (101 females and 79 males) were caught. The fish were examined for Clinostomum metacercariae by cutting the ventral side from the anal opening to the lower jaw. The gill chambers were examined and inspected visually to detect macroscopic parasites. Of the 180 fish collected during the study, 113 (62.8%) were infected by 284 Clinostomum larvae in the cranial cavity while 67 fish were not infected. Among the infected fish, 46 were males and 67 were females. Greater parasite burden and mean intensity were observed in female fish (2.7 MI) than males (2.2 MI). There was no statistically significant difference in mean intensity of infection between male and female fish (n=180; t=0.521; p<0.05). Uninfected fish were in a poorer condition than infected fish in July and October only. The lowest monthly condition factor for both infected (1.8) and uninfected (1.7) fish occurred in October. The monthly condition factors for both infected (1.94–3.51) and noninfected fish (1.81–5.28) were greater than 1. For prevalence by total length groups, highest prevalence (66.3%) was recorded in the medium length group (10–12 cm) and lowest (25.0%) in the (16–18 cm) length group. Highest mean intensity (2.8) and parasite density (146 parasites) was observed in the length group (13–15 cm) and lowest mean intensity (1.0) in larger length groups (16–18 cm and above 19 cm). Highest abundance (1.74) was recorded in the length group 13–15 cm and lowest abundance (0.25) in the length group 16–18 cm. Parasite burden was positively correlated to fish size (total length). It was concluded that Clinostomum metacercariae are a common parasite in Oreochromis mossambicus in Mashoko dam.